2021
DOI: 10.5826/dpc.1103a49
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome and Its Parameters and Their Correlations With Psoriasis Duration, Severity, and Sleep Quality In Psoriasis Patients: A Cross-Sectional Study

Abstract: Background: Psoriasis is an inflammatory skin disease that may lead to comorbidities, including metabolic syndrome (MS). Objective: We determined the prevalence of MS and its correlation with psoriasis duration, severity, and sleep quality in psoriasis patients. Methods: A total of 112 subjects with chronic plaque psoriasis were studied. Demographics, MS parameters, disease duration, severity, and sleep quality were examined. The Psoriasis Area and Severity Index (PASI)and the Pittsburgh Sleep Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The results endorse and extend the findings of prior research showing a high prevalence of SD in patients with psoriasis. Recently, Tas and Kabeloglu 11 and Sahin et al . 12 separately found that the percentage of SD (PSQI score of >6) was 84.8% and 59.0%, which was higher than the 47.9% observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results endorse and extend the findings of prior research showing a high prevalence of SD in patients with psoriasis. Recently, Tas and Kabeloglu 11 and Sahin et al . 12 separately found that the percentage of SD (PSQI score of >6) was 84.8% and 59.0%, which was higher than the 47.9% observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…[7][8] Limited research has shown that psoriatic arthritis, the Psoriasis Area and Severity Index (PASI), depression, age, female sex, and the duration of psoriasis are associated with sleep in patients with psoriasis. [9][10][11][12][13] However, no study has examined the prevalence of SD and the factors affecting SD in Chinese patients with psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Different conclusions have been reached about the age, age at onset, and disease course of patients with psoriasis complicated by MS. Studies have shown that patients with MS are older, have an older age at onset, and have a longer disease course than patients without MS. 22 However, Chularojanamontri et al . 23 and Salunke et al .…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies on lifestyle interventions that affect sleep and investigate respective effects on disease activity are lacking ( 299 ). Impairment of sleep in patients with psoriasis, psoriatic arthritis and axial SpA increases the risk for psychiatric diseases, which themselves might impair sleep, resulting in a vicious circle ( 300 302 ). Moreover, patients with psoriasis and sleep disturbances have a higher risk of stroke and ischemic heart disease compared to psoriatic patients without sleep disturbances ( 303 ).…”
Section: Epidemiological and Experimental Evidence That Shift Work Co...mentioning
confidence: 99%